Improvement of Teacher Professionalism through Classroom Action Research Training in MGMP Kimia SMA/ MA Kabupaten Tanah Datar - Yerimadesi Yerimadesi; Ellizar Jalius; Faizah Qurrata Aini (Fakultas MIPA Universitas Negeri Padang, 2020)
Classroom Action Research (CAR) is one of the activities which teachers must carry out to improve and develop their professionalism. This community service activity aimed at train and improve the professionalism of chemistry teachers through CAR activities. The method was conducted with lectures, discussions, questions and answers, and workshops on proposal preparation, literature searching, CAR implementation, report, and CAR research articles preparation. The number of participants is 34 who are the members of MGMP Kimia Kabupaten Tanah Datar. There were six meetings with the total time was 36 hours in July-December 2019. The instrument used was a questionnaire. The data obtained were analyzed using the percentage and equation techniques of Kappa Cohen's. Based on the results, of the 34 participants, 15 CAR titles were obtained, 11 CAR titles were carried out, 8 CAR reports were produced, and 4 CAR articles were drafted. Based on the teacher's questionnaire responses, the kappa moment average value was 0.86 which categorized as very high. This data showed that the classroom action training activities provided can improve the professionalism of chemistry teachers in preparing proposals, implementing, drafting reports and articles. This training activity still needs to be continued to obtain CAR articles that have been published in several national /international journals or proceedings.